Project-Based Learning in the Perspective and Approach of Progressive Education Philosophy - Lutfi Lutfi; Abdullah Sinring; Syamsu Kamaruddin (Universitas Muhammadiyah Gresik, 2024)
This research aims to analyse the implementation of project-based learning in the context and approach of progressive education philosophy with a focus on the challenges and opportunities faced by educators in implementing this learning model in the classroom. Through literature review and analysis, it was found that although project-based learning provides an opportunity to increase student engagement and develop critical thinking skills, there are a number of challenges such as lack of professional support, time constraints and lack of adequate resources. The findings suggest that the fit between learning strategies and objectives is crucial to ensure the effectiveness of this learning model. The significance of the results of this study lies in its contribution to the understanding of the role of project-based learning in progressive education, as well as how its application can improve the quality of learning in a wider context. The implications of this study suggest the need for better training for educators as well as stronger institutional support to optimise the use of this learning model, in the hope that it can positively influence the development of student competencies and encourage innovation in educational practices.